Effect of plasma components on the stability and permeability of microcapsule. Issue 7 (16th September 2013) - Chen, Li; Zhang, Ying; Li, Shen; Wang, Xiuli; Li, Na; Wang, Yu; Guo, Xin; Zhao, Shan; Yu, Weiting; Sun, Guangwei; Liu, Yang; Ma, Xiaojun
Abstract Immobilization of hepatocytes in microcapsules has been a potentially alternative methodology for bioartificial livers (BALs). Moreover, the stability and permeability are the key parameters of these microcapsules. However, these alginate‐based microcapsules are unstable if the surrounding medium disrupts the ionic interactions between alginate and the polycation. As hundreds of components are included in human plasma, the stability and permeability in plasma of microcapsules need to be sufficiently investigated. In the present study, the stability of three kinds of alginate‐based microcapsules was evaluated when they were immersed in plasma. Our results showed that stability of alginate‐α‐poly (l‐lysine)‐alginate (α‐APA) microcapsules was well maintained, better than those of alginate‐ε‐poly (l‐lysine)‐alginate (ε‐APA) and alginate–chitosan–alginate (ACA) microcapsules. Also, factors affecting the stability of microcapsules in plasma were analyzed and it showed that heparin was the key factor that affected the stability of α‐APA microcapsules, whereas heparin and low molecular electrolytes such as HCO3− and H2PO4−/HPO42− were the factors to ε‐APA and ACA microcapsules. In addition, the permeability evaluation showed no decrease in permeability of microcapsules after incubation in plasma. Our study might provide a foundation for the selection and modification of materials for microcapsule‐based BAL devices. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2408–2416, 2014.